Severe, Moderate, and Mild Wear Performance of Deep Cryogenically Treated D3 Tool Steel Against Al2O3, 100Cr6, and 316 Stainless Steel Balls - Boztepe, Alican; Özer, Gökhan; Gecü, Rıdvan (Springer Nature, 2025)
This study investigates the effects of severe, moderate, and mild wear behavior of cryogenically treated and double-tempered AISI D3 cold-work tool steel under varying wear conditions. Cryogenic treatment was performed at 196 C for 18 hours and each tempering step was carried out at 250 C for 2 hours. Three different balls—Al2O3, 100Cr6, and 316 stainless steel—and three different loads—5, 10, and 15 N—were used in dry sliding tests. Microstructural and tribological analyses were conducted using FESEM and EDS techniques. The cryogenic treatment facilitated the transformation of retained austenite into martensite, while double tempering promoted the formation of M7C3 and M23C6-type carbides. Regardless of the ball used, increasing the load increased the wear losses due to the enhanced contact pressure. The Al2O3 ball resulted in abrasive wear, while 316 stainless steel caused extremely high galling between tribopairs. Abrasive, adhesive, and oxidative wear occurred in the D3 tool steel samples slid against 100Cr6 steel, providing a mild wear regime, although it was chosen to simulate moderate wear conditions. Considering the wear losses of both cryogenically treated AISI D3 tool steel and its counterparts used, the 100Cr6 ball resulted in the lowest wear losses.